SOURCES ON MALAYSIAN DISSERTATIONS AND ACADEMIC RESEARCH ACTIVITIES - Awang Ngah, Zainab; Teh, Kang Hai (Malaysian Journal of Library and Information Science, 1998)
Identifies available sources of information on Malaysian dissertations submitted to local or foreign universities and held at the various research and academic libraries. Includes published sources reporting and listing research activities comprising general and specialised bibliographies and listings of published research and consultancy work undertaken (include articles published in journals, papers presented at conference proceedings, books and research reports authored, edited, translated and compiled). The local universities are the main publishers of such listings while government agencies and research institutions contribute sporadic titles. The distributed efforts by the various institutions clearly hinder the visibility and access to such materials. Suggests closer collaboration among publishers involved to make a union database a reality.